Production of Low-Fat Mayonnaise With the Interaction Between Citrus Fiber and Hydrocolloid Gums - Akalin, B.; Yilmaz, E. Genc; Cakmak, Z. H. Tekin; Karasu, S.; Toker, O. S.; Ozturk, S. Akyil (WILEY, 2026)
This study investigated the potential use of citrus fiber (CF) and hydrocolloid gums-Arabic gum (AG), guar gum (GG), and xanthan gum (XG)-to improve the microstructure, emulsion, and oxidative stability of low-fat mayonnaise. The rheological parameters, flow behavior, viscoelastic, and 3-ITT properties of mayonnaise samples were analyzed. All formulations exhibited shear-thinning behavior, solid-like characteristics, and recovery ability, indicating viscoelastic structures. According to the Power Law model, the flow behavior index (n) and consistency index (K) ranged from 0.115 to 0.763 and 0.056 to 363.277 Pa s(n), respectively. Mayonnaise samples containing both CF and gums showed lower n and higher K values than controls, suggesting that CF enhanced shear-thinning behavior. Increasing CF concentration was positively correlated with K values, indicating improved structural strength. Samples formulated with 1%AG-3%CF, 0.5%GG-2%CF, and 0.35%XG-2%CF exhibited higher storage (K ') and loss (K '') moduli compared to low-fat controls, confirming a synergistic effect between CF and the gums. Oxidative stability, evaluated by the OXITEST method, revealed that CF-containing samples had higher induction period (IP) values than both low-fat and high-fat commercial mayonnaise. Overall, the interaction of CF with AG, GG, and XG improved the rheological behavior, emulsion stability, and oxidative resistance of low-fat mayonnaise, indicating that citrus fiber-gum systems can serve as promising functional ingredients for developing healthier emulsion-based products.
Keywords: citrus fiber; emulsion and oxidative stability; gum; mayonnaise; microstructural properties; REPLACER; Engineering; Food Science & Technology